(untitled) (Philological Studies, 2019)
In this article we analyse women’s identities on the Balkans in the XIX century. Self- discovery was a process the educated women experienced first, so that they could emphasise their identity. They wanted to play a role in public life, and they sought and defended the right to it through women’s associations, through a large number of articles in newspapers and magazines, through poetry, prose and plays, i.e. through literature in general.